KOMPOSISI PROKSIMAT HIJAUAN PAKAN YANG DIBUDIDAYAKAN DI SENTRA PERTANIAN TERPADU PT. ARUTMIN INDONESIA SITE ASAM-ASAM - Wenni Meika Lestari; Bunga Putri Febrina; Dwi Sandri; Endang Wawan (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
This study was aimed to identify the chemical composition of forages cultivated in the Centre of Integrated Farming of PT. Arutmin site Asam-asam including Indigofera, Odot, Gamal, Azolla, and Singkong. Dry Matter (DM), Organic Matter (OM), Crude Fibre (CF), Crude Protein (CP), and Ether Extract (EE). Each sample was analyzed in The Laboratory of Analysis, Politeknik Negeri Tanah Laut. Analysis of the parameters were carried out using the descriptive method. Proximate analysis showed that indigofera, odot, gamal, azolla and singkong contained 97,3%; 96,1%; 98,2%; 94,6%; 92,6% of DM, 87,9%; 82,4%; 91,3%; 79,2%; 86,7% of OM, 16,0%; 31,5%; 21%; 25,7%; 28,3% of CF, 16,0%; 20,2%; 15,8%; 21,1%; 19,5%; 22,7% of CP, and 1,5%; 3,2%; 2,7%; 5,5%; 2,3% of EE respectively. In conclusion, the chemical composition of the forages cultivated in the Centre of Integrated Farming varies from one plant to another.